Vibration parameters affecting vibration-induced reflex muscle activity. (2nd January 2017) - Cidem, Muharrem; Karacan, Ilhan; Cakar, Halil Ibrahim; Cidem, Mehmet; Sebik, Oguz; Yilmaz, Gizem; Turker, Kemal Sitki; Karamehmetoglu, Safak Sahir
Abstract: Purpose: To determine vibration parameters affecting the amplitude of the reflex activity of soleus muscle during low-amplitude whole-body vibration (WBV). Materials and methods: This study was conducted on 19 participants. Vibration frequencies of 25, 30, 35, 40, 45, and 50 Hz were used. Surface electromyography, collision force between vibration platform and participant's heel measured using a force sensor, and acceleration measured using an accelerometer fixed to the vibration platform were simultaneously recorded. Results: The collision force was the main independent predictor of electromyographic amplitude. Conclusion: The essential parameter of vibration affecting the amplitude of the reflex muscle activity is the collision force.